Ontology-driven nursing practice: a case report in family nursing - Bruna César-Santos; Maria Joana Campos; Fernanda Bastos (Millenium)
Introduction: This ontology-driven nursing practice focuses on the family as a unit while also considering individual needs and promoting personalized and inclusive care.